A REORGANIZAÇÃO DA POLÍCIA NO ESTADO DO PARANÁ NOS ANOS 1950 (Revista de História Regional, 2007)
This article has the purpose of analyzing the reorganization of the police in the State of Paraná, between 1950-1960.